Differential impact of the expression of the androgen receptor by age in estrogen receptor–positive breast cancer. (30th September 2013) - Tokunaga, Eriko; Hisamatsu, Yuichi; Taketani, Kenji; Yamashita, Nami; Akiyoshi, Sayuri; Okada, Satoko; Tanaka, Kimihiro; Saeki, Hiroshi; Oki, Eiji; Aishima, Shinichi; Oda, Yoshinao; Morita, Masaru; et al.
Abstract We evaluated the expression of the androgen receptor (AR) to determine its significance in breast cancer. AR expression levels were analyzed in 250 invasive breast cancers by immunohistochemistry and any association with the clinicopathological features was evaluated. AR expression was higher in estrogen receptor (ER)‐positive cases than in ER‐negative cases (P < 0.0001). AR expression was associated with ER level, and it increased with age in ER‐positive cases. The cut‐off value was determined to be 75% (Cancer Res. 2009;69:6131–6140), and AR expression was considered to be high in 155 (62%) cases. High AR expression significantly correlated with lower nuclear grade (P < 0.0001), ER and progesterone receptor (PR) positivity (P < 0.0001 and P = 0.0022), HER2 negativity (P = 0.0113), lower Ki67 index (P < 0.0001) and a longer disease‐free survival (DFS) and distant metastasis‐free survival (DMFS) (P = 0.0003 and 0.0107). This association between a high AR expression and a good DFS and DMFS was significant for ER‐positive tumors (P < 0.0001 and P = 0.0018); however, no association existed between AR expression and prognosis for ER‐negative tumors. In patients ≤51 years old, a high AR expression level significantly correlated with a better prognosis, but this was not significant in patients who were 50 or younger. Multivariate Cox hazard analyses revealed AR expression to be independently associated with a good prognosis in overall patients (HR 0.46, P = 0.0052) and in the ER‐positive cohort (HR 0.34, P = 0.0009). AR expression is associated with a less aggressive phenotype and a good prognosis in patients with ER‐positive breast cancer. This is considered to be a specific phenomenon for postmenopausal breast cancer patients.